(untitled) (CAHIERS MAGELLANES-NS, 2024)
Jayakwadi dam built in 1976, is located in Jayakwadi village in Paithan taluka of Chhatrapati Smbhaji Nagar district in Maharashtra, India. Monitoring the water quality of Jayakwadi Dam is important task because the main purpose of dam water is for drinking water for Chhatrapati Sam haji Nagar city people. The water quality is easily estimated with the help of remote sensing and GIS technique. The data used to estimate water quality is Landsat-8 and Sentinal-2 satellite multispectral data. Sentinal-2 is high resolution data than the Landsat-2 data. We used mainly data form 2016 to 2023. NDWI, NDTI, NDCI ratio indices mainly used to estimate water quality. Turbidity can be easily estimated with the help of NDTI indices while chlorophyll can also be estimated with the help of NDCI. The water surface area can be easily estimated with the help of NDWI. In this paper we try to find out water quality of reservoir and can be easily estimated with the help of Indices. NDTI and NDCI shows good results for turbidity and chlorophyll concentration. With the help of optical property satellite data we can easily determine water quality by indices of bands.